The Pengaplikasian Metode K-W-L untuk Meningkatkan Pemahaman Membaca Di Kelas III: Pengaplikasian Metode K-W-L untuk Meningkatkan Pemahaman Membaca Di Kelas III - Alya Romadhona, Fenny; Alfin, Jauharoti (Jurnal Teladan: Jurnal Ilmu Pendidikan dan Pembelajaran, 2023)
The annexation of students' reading comprehension skills is very helpful in improving student learning outcomes, so that reading skills must be mastered by students who are in elementary school. descriptive qualitative method with a case study approach. Data collection techniques obtained from observation, tests, and interviews. The observation process is intended to obtain responses from the subjects and objects of research on the ongoing learning process. The interview process aims to obtain more detailed data regarding the application of the K-W-L method. On the test technique to obtain the extent to which the learning outcomes obtained by students after using the K-W-L method for Indonesian language material. The data analysis technique used was Milles's technique, namely 1) Putting together all primary data and secondary data, primary data was obtained from observations and tests and secondary data was obtained from the results of interviews conducted by researchers with class III teachers. 2) Data reduction or classification and elimination of data that is less needed by researchers. 3) Presentation of data, namely describing data descriptively. 4) Draw final conclusions. The results of the research are the application of the K-W-L method in learning Indonesian which is able to improve students' reading comprehension skills. This is evidenced by the average Pre-Test score of 70 increasing to 82.40. So it was concluded that the K-W-L method increased student learning outcomes in terms of the KKM limit that was exceeded, namely 31.60% to 84.20%.